2012
DOI: 10.1104/pp.112.206706
|View full text |Cite
|
Sign up to set email alerts
|

RRP41L, a Putative Core Subunit of the Exosome, Plays an Important Role in Seed Germination and Early Seedling Growth in Arabidopsis    

Abstract: In prokaryotic and eukaryotic cells, the 39-59-exonucleolytic decay and processing of RNAs are essential for RNA metabolism. However, the understanding of the mechanism of 39-59-exonucleolytic decay in plants is very limited. Here, we report the characterization of an Arabidopsis (Arabidopsis thaliana) transfer DNA insertional mutant that shows severe growth defects in early seedling growth, including delayed germination and cotyledon expansion, thinner yellow/pale-green leaves, and a slower growth rate. High-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
(56 reference statements)
0
23
0
Order By: Relevance
“…Indeed, an ATPdependent RNA helicase eIF4A accumulated during PEG soaking and general osmopriming as well as DEAD box RNA ATP-dependent helicase 7 whose gene was up-regulated during general osmopriming (Table 2) may play pivotal role in modulation of RNA metabolism. Moreover, mRNA decay is also important since impairment in the RRP41L, a putative core subunit of the exosome, delays germination and inhibits seedling growth [41]. Gene coding for RRP41L was up-regulated in osmoprimed seeds ( Table 2).…”
Section: Protein Synthesis Potential Post-translational Processing Cmentioning
confidence: 98%
“…Indeed, an ATPdependent RNA helicase eIF4A accumulated during PEG soaking and general osmopriming as well as DEAD box RNA ATP-dependent helicase 7 whose gene was up-regulated during general osmopriming (Table 2) may play pivotal role in modulation of RNA metabolism. Moreover, mRNA decay is also important since impairment in the RRP41L, a putative core subunit of the exosome, delays germination and inhibits seedling growth [41]. Gene coding for RRP41L was up-regulated in osmoprimed seeds ( Table 2).…”
Section: Protein Synthesis Potential Post-translational Processing Cmentioning
confidence: 98%
“…The following mutants have been used in different experiments: sr30 (GK325-E11, N322146), lba1 (Yoine et al, 2006), upf3-1 (Hori and Watanabe, 2005), 35S: HF-RPL18 (N66056; Zanetti et al, 2005), sop2-1 (Hématy et al, 2016), mtr3 (also referred to as rrp41l; Yang et al, 2013), hen2-4 and mtr4-1 (Lange et al, 2011), ski2-6 (Zhao andKunst, 2016), xrn4-5 (Souret et al, 2004), and xrn2-1 xrn4-6, xrn3-3 xrn4-6, and fry1-6 (Gy et al, 2007). The following genes have been analyzed: AT1G09140 (SR30), AT2G37340 (RS2Z33), AT5G37055 (SEF), AT1G13320 (PP2A), and At5G09810 (ACTIN7).…”
Section: Accession Numbersmentioning
confidence: 99%
“…In addition, in vitro experiments on maize seed germination showed that stored mRNAs are preferentially translated by the eIF(iso)4E isoform, a component of the cytoplasmic mRNA cap-binding complex (eIF4F) (124,131). Finally, mRNA decay is of importance because impairment in the 3Ј-5Ј exonuclease RRP41L delays germination and inhibits seedling growth (132). In the rrp41l knockout mutant, the mRNA levels of genes characteristic of the late maturation program (e.g.…”
Section: Constitutive De Novo Synthesis Of Enzymes Involved In Energymentioning
confidence: 99%